2액실 바이폴라막 전기투석에 의한 폐 Na2SO4 용액에서 NaOH 재생 - 이영재; 서민혁; 안재우 (대한금속·재료학회지, 63(4), 2025)
With the recent introduction of various environmental policies focused on carbon neutrality has maderecycling a crucial task in the electric vehicle industry. In particular, the recycling of lithium-ion batteries, acritical component of EVs, is becoming increasingly important. The process of recovering valuable metals suchas lithium (Li), cobalt (Co), manganese (Mn), and nickel (Ni) from spent batteries typically involves leaching,precipitation, solvent extraction, and crystallization. However, these processes generate a significant amount ofNa2SO4 wastewater. To address this issue, bipolar membrane electrodialysis (BMED) has been developed torecover H2SO4 and NaOH from Na2SO4. The conventional method uses a three-compartment configuration tosimultaneously recover acid and base components, This approach, however has drawbacks such as high initialinstallation costs due to the expensive membranes and low current efficiency. To overcome these limitations, atwo-compartment constant voltage method using cation exchange membranes and bipolar membranes wasemployed in this study. The effects of various process parameters on the recovery rate of NaOH, currentefficiency, flux, and energy consumption were evaluated. Based on the optimal conditions from the experiment,a flow rate of 950 mL/min, a feed solution of 1.30 M Na2SO4 at 1.5 L, and an initial base solution of 0.1 M NaOHat 0.50 L resulted in an base recovery rate of 67.59%, with 0.91 L of 2.96 M NaOH recovered. KCI Citation Count: 0